Platelet-promoting drug delivery efficiency for inhibition of tumor growth, metastasis, and recurrence - Li, Xiaoliang; Hu, Lanyue; Tan, Chengning; Wang, Xiaojie; Ran, Qian; Chen, Li; Li, Zhongjun (Frontiers in Oncology, 2022)
Nanomedicines are considered as a strategy for anticancer therapy, however, the low targeting efficiency in vivo is a great obstacle for their clinical application. Camouflaging nanomedicines with platelet membrane (PM) or platelet would significantly prolong the retention time in bloodstream, enhance the targeting ability to tumor cells and reduce the off-target on the major orangs due to the natural properties of platelet in the vivo application. In the current review, the advances of PM or platelet as smart carriers to deliver nanomedicines for the inhibition of tumor growth, metastasis and recurrence were summarized. And the opportunities and challenges of this camouflaging strategy for anticancer treatment were also discussed